(4x+17)=(5x-1)

Simple and best practice solution for (4x+17)=(5x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+17)=(5x-1) equation:


Simplifying
(4x + 17) = (5x + -1)

Reorder the terms:
(17 + 4x) = (5x + -1)

Remove parenthesis around (17 + 4x)
17 + 4x = (5x + -1)

Reorder the terms:
17 + 4x = (-1 + 5x)

Remove parenthesis around (-1 + 5x)
17 + 4x = -1 + 5x

Solving
17 + 4x = -1 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
17 + 4x + -5x = -1 + 5x + -5x

Combine like terms: 4x + -5x = -1x
17 + -1x = -1 + 5x + -5x

Combine like terms: 5x + -5x = 0
17 + -1x = -1 + 0
17 + -1x = -1

Add '-17' to each side of the equation.
17 + -17 + -1x = -1 + -17

Combine like terms: 17 + -17 = 0
0 + -1x = -1 + -17
-1x = -1 + -17

Combine like terms: -1 + -17 = -18
-1x = -18

Divide each side by '-1'.
x = 18

Simplifying
x = 18

See similar equations:

| x^2-86x+1320=0 | | 3X^3=15 | | (3)(12)+8x=86 | | 16+8y=12y | | 3*-14+4*y=12 | | 4(5x+3)=28 | | x-45+150=180 | | -4x-1/3=35/3 | | x+4+132=180 | | (3y+8)=(6y-1) | | 4x-1/3=35/3 | | 6x+(2)(15)=150 | | -5y+6=-7y-14 | | (6x)=(5x+9) | | 8y-3=5(y+6) | | 3x-20=6x-8 | | 10+3y=-6 | | S=Ngj | | 3(2+x)=-36 | | x^2-2400=0 | | -2g-6=-9 | | 360=(6+3w)(w) | | 18+0.5x=25 | | 3(2c-5)+2c= | | -8w-2=-10-4w | | 4x+6-x=22+6 | | -1/3(9s-36t=-5)= | | 24+2X=110 | | -5+3y=-6 | | 5p-2q=3m+d | | -7(x+2y+5z)= | | 11a+b=5a+24 |

Equations solver categories